The prevailing organizational climate of vocational schools in Baghdad governorate from the point of view of the teaching staff (Journal of the College of Basic Education, 2023)
Some countries of the world have paid great attention to education, due to its importance in the lives of peoples, so they allocated huge amounts of money for it in their budgets as they prepared highly experienced cadres for it, and modified their strategies and plans to suit their educational aspirations because the educational process is an integrated system whose components are governed by a set of interrelationships among them.And that the success of educational systems is linked to one variable, the nature of the work of the systems and the network of relationships and interactions that activate through its sub-components affect the success of educational systems and the achievement of the goals and objectives that they seek. The work atmosphere and the climate in which the workers in the educational system live constitute an effective variable in the degree and level of performance of this system and in the feeling of the interactors through its various sub-components of comfort, reassurance, confidence, and the desire to exert their utmost efforts in their endeavor to fulfill the requirements of their roles. Therefore, it is noted that there is a relationship between the work atmosphere that The organization prevails, which is called (the organizational climate) and the satisfaction of the employees within the organization with it, as the success of the system is directly proportional to the degree of correctness of the work climate that prevails in it.